Sympathetic ablation combined to dorsal ganglion modulation was cost-effective for Complex Regional Pain Syndrome-1 - Trindade, Carlos A. F.; Oliveira, Célia S; Serra, Thiago S; Defino, Helton A.; Lauretti, Gabriela R. (International Journal of Advanced Engineering Research and Science, 2022)
Sympathetic ablation combined to dorsal ganglion modulation was cost-effective for Complex Regional Pain Syndrome-1. Background: In Complex Regional Pain Syndrome-1 (CRPS), sympathetic ganglion block followed by radiofrequency (RF) is the treatment of choice. However, data suggest that dorsal ganglion (DG) is partly responsible for its central pain sensitization. The study aimed to evaluate the cost-effectiveness of central desensitization combined to either blocks or RF at the same levels. Methods: 36 patients with lower extremity CRPS-1 were randomly assigned to 1 of 2 Treatments (n=18). After effects of the first selected treatment receded, patients were crossed over to the second treatment. The treatments were : 1) test blocks followed by 4-weekly L3 sympathetic block + epidural sacral block or 2) test blocks followed by L3-L4-L5 sympathetic ablation + L3-L4-L5 DG modulation RF. Time of analgesia was defined as VAS>3cm. Patients acted as their own control related to analgesia, routine activities, sleep pattern and costs. Results: 24 patients completed the study. The analgesia time after the 4-weekly blocks were 5±1 months and the annual costs USA5000. Analgesia time after RF was 15±2 months (p<0.001) and costs reduced by 23% in the first year and 32%-36% in the following years extrapolation. Quality of life and sleep pattern improved during the analgesia period (p> 0.05). Discussion: Sympathetic ganglion combined to DR RF at the same levels (L3-L4-L5) resulted in 15-month compared to 5-month analgesia after the classical 4-weekly blocks, and improved physical capacity and sleep pattern. It was cost-effective, and reduced rates by 23% during the first-year evaluation, followed by 32%-36% cost reduction in following years, by extrapolation.